Cryopreservation of Coffea liberica Seeds and Embryos following desiccation and freezing treatments - Y. L., Hor; P. C., Stanwood; H. F., Chin (Universiti Putra Malaysia Press, 1993)
Desiccation of Coffea liberica seeds for 6 days in an air-conditioned room reduced seed and attached emltryo moisture from 52.58% and 47.49% to 14.58% and 12.56% respectively. Seed germination and viability of the attached emltryo were maintained at moderate levels of 66% and 38% respectively. However, none of the desiccated seeds or embryos survived freezing in liquid nitrogen. Excised emltryos desiccated in the lamina flow cabinet lost their moisture very rapidly from 36.8% to 9.27% within 1.5 hours. More than 70% of these emltryos survived the desiccation. Moreover, partially desiccated emltryos at 17.17% moisture or less survived subfreezing temperatures. Between 35% to 50% survived slow freezing to -3ffC, but this was reduced to approximately 30% when they were subsequently plunged into liquid nitrogen. Fast freezing by direct plunge into liquid nitrogen also resulted in 10% to 35% survival. Desiccation ofexcised coffee embryos for 0.5h to 17.17% moisture was optimal for eryopreservation, irrespective of the speed offreezing. Differential thermal analyses of seed tissues suggest that the absence of freezable water is an important factor for successful eryopreservation of excised coffee emltryos. However, the importance of initial vigour, moisture variation and recovery media is also discussed.